THE BIOPHYSICAL BASIS AND CLINICAL SIGNIFICANCE OF CONTINUOUS GLUCOSE MONITORING (CGM) SYSTEMS (The New Uzbekistan Journal of Medicine, 2025)
Continuous Glucose Monitoring (CGM) systems represent a major advancement in diabetes management by enabling real-time tracking of glucose levels. This article explores the biophysical principles underlying CGM technologies, including sensor mechanisms, interstitial glucose measurement, and data transmission methods. Additionally, the clinical importance of CGM is discussed in the context of early hypoglycemia detection, improved glycemic control, and enhanced patient quality of life. The article also considers the potential applications of CGM in pediatric and intensive care settings, emphasizing the role of digital health technologies in modern medical practice.